2020
DOI: 10.1007/s12192-020-01107-y
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific effects of temperature on proteasome function

Abstract: Variation in ambient growth temperature can cause changes in normal animal physiology and cellular functions such as control of protein homeostasis. A key mechanism for maintaining proteostasis is the selective degradation of polyubiquitinated proteins, mediated by the ubiquitin-proteasome system (UPS). It is still largely unsolved how temperature changes affect the UPS at the organismal level. Caenorhabditis elegans nematodes are normally bred at 20 °C, but for some experimental conditions, 25 °C is often use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Our previous research has demonstrated that UPS activity varies in a tissue-specific manner in live C. elegans , and is affected by aging and stress, such as proteasomal impairment and elevated growth temperature [ 31 , 32 , 35 ]. The rate of autophagic flux has also been reported to vary in different C. elegans tissues [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous research has demonstrated that UPS activity varies in a tissue-specific manner in live C. elegans , and is affected by aging and stress, such as proteasomal impairment and elevated growth temperature [ 31 , 32 , 35 ]. The rate of autophagic flux has also been reported to vary in different C. elegans tissues [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…NL2099[ rrf-3(pk1426)II ] mutant strain was a kind gift from Dr. G. Wong (University of Eastern Finland). YD116[ rrf-3(pk1426);xzIs2[unc-54p::UIM2::ZsProSensor] ] reporter strain was generated by crossing NL2099[ rrf-3(pk1426)II ] strain with YD114[ xzIs2[unc-54p::UIM2::ZsProSensor] ] [ 35 ]. Information on the cloning of the plasmid has been described previously in Matilainen et al, 2013, as a precursor for the YD90[ xzIs1[vha-6p::UIM2::ZsProSensor] ] strain [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Surprisingly, a change in ambient temperature from 20 to 25°C can affect selective protein degradation via the UPS. UPS activity increases in the intestine but not in muscle cells, suggesting tissue-specific regulation of protein degradation ( Pispa et al, 2020 ). Increasing temperature conditions also modulates mRNA translation.…”
Section: The Influence Of Temperature On Proteostasismentioning
confidence: 99%
“…The heat-shock-stressed cells also contained a 2-fold higher amount of the proteasome activator 11S, and the extent of the bound activator was doubled in early-and mid-passage cells only. Recent studies showed that C. elegans exhibits tissue-specific responses of the ubiquitin-proteasome system (UPS) as an organismal strategy to cope with a rise in ambient temperature [90]. An ambient temperature shift from 20 to 25 • C increased UPS activity in the intestine but not in the body wall muscle tissue, where a concomitant accumulation of polyubiquitinated proteins occurred.…”
Section: Effect Of Temperature Variationmentioning
confidence: 99%